Expedient Synthesis of gem-CF2-2H-Thiophenes from Enaminothiones - Zhang, Xinyu; Zhang, Xuheng; Fu, Rui; Zhang, Zhengyu; Jiang, Yaojia (Synlett, 2024)
An expedient and easy-to-handle synthetic platform has been established for the constructing of 2H-thiophenes carrying fluorine atoms through [4+1] cyclization of enaminothiones with fluorinated carbene precursors. This simple reaction system is well compatible with a wide range of substrates under completely metal-free conditions. The resulting 2H-thiophenes can undergo further late-stage modifications to yield a wide range of fluorine-substituted heterocycles.
Keywords: carbene chemistry; [4+1] cyclization; enaminothiones; fluorinated 2H-thiophenes; difluorocarbene